Activation of hypothalamic astrocytes suppresses feeding without altering emotional states. Issue 12 (23rd September 2016) - Sweeney, Patrick; Qi, Yong; Xu, Zhenping; Yang, Yunlei
Abstract : Emerging evidence shows that hypothalamic astrocytes react to and counteract energy surfeit produced by high‐fat diet (HFD) feeding. However, the functional role of astrocytes in the control of energy states and the underlying molecular mechanism(s) during physiological conditions remain largely underexplored. In the present study, by taking advantage of spatiotemporally precise optogenetic approaches, real‐time measurements of extracellular adenosine, and behavioral assays, we find that optogenetic stimulation of astrocytes localized in the medial basal hypothalamus (MBH) suppresses food intake in a frequency dependent manner with high frequency, but not low frequency, stimulation of astrocytes reducing food intake. Furthermore, stimulation of MBH astrocytes diminishes orexigenic ghrelin or fasting‐induced hyperphagia without effecting anxiety‐related behavior. Consistent with a frequency dependent role for MBH astrocytes in feeding behavior, optogenetic stimulation of MBH astrocytes increases extracellular levels of adenosine in a frequency dependent manner. Collectively, our results provide new insights into the role of astrocytes in physiological functions during naturally occurring behaviors, such as feeding. GLIA 2016;64:2263–2273 Main Points: Activity‐dependent adenosine‐mediated suppression of food intake. Activity‐dependent astrocytic elevation of extracellular adenosine. Activation of astrocytes did not effect anxiety‐related behaviors.